Closed medial subtalar dislocation: A case report and literature review - Amine El Farhaoui; Mohamed Maroc; Zakaria Khatab; Anass Sefti; Mbainaidara Debonheur; Adnane Lachkar; Najib Abdeljaouad; Hicham Yacoubi (Trauma Case Reports)
Subtalar dislocation is characterized by simultaneous dislocation of the subtalar (talocalcaneal) and talonavicular joints, hence the name talocalcaneonavicular. These lesions can be grouped into four distinct categories: anterior and posterior, which are exceptional, lateral and medial. Medial subtalar dislocations are more frequent, are due to low-energy trauma and generally have good functional results. Anatomical reduction and stabilization of the subtalar joint and optimal management of all associated foot injuries are the key to good results.